Longitudinal Analysis Between Maternal Feeding Practices and Body Mass Index (BMI): A Study in Asian Singaporean Preschoolers - Quah, Phaik Ling; Ng, Jing Chun; Fries, Lisa R.; Chan, Mei Jun; Aris, Izzuddin M.; Lee, Yung Seng; Yap, Fabian; Godfrey, Keith M.; Chong, Yap-Seng; Shek, Lynette P.; Tan, Kok Hian; Forde, Ciaran G.; et al. (Frontiers in Nutrition, 2019)
Bidirectional studies between maternal feeding practices with subsequent child weight are limited, with no studies in Asian populations. In longitudinal analyses, we assessed the directionality of the associations between maternal feeding practices and body mass index (BMI) in preschoolers. Participants were 428 mother child dyads from the GUSTO (Growing Up in Singapore Towards healthy Outcomes) cohort. Feeding practices were assessed using the Comprehensive Feeding Practices Questionnaire (CFPQ) at age 5 y. Child BMI was measured at ages 4 and 6 y. BMI and maternal feeding practices subscales were transformed to SD scores and both directions of their associations examined with multivariable linear regression and pathway modelling. Higher BMI at age 4 was associated with lower encouragement of balance and variety (β=-0.33; 95%CI: -0.53,-0.13), lower pressure to eat (β=-0.49; -0.68, -0.29) and higher restriction (β=1.10; 0.67, 1.52) at age 5, adjusting for confounders and baseline feeding practices at 3 years. In the reverse direction, only pressure and restriction at age 5 were associated with lower and higher child BMI at age 6 years, respectively but were attenuated to non-significance after adjustment for baseline BMI at age 5 (β=0.01 (-0.01, 0.03); β=0.02 (0.002, 0.03), respectively). Associations of child BMI with maternal restriction and pressure feeding practices was stronger than the reverse association (Wald’s statistics = 24.3 and 19.5, respectively; p<0.001). The strength and directionality suggests that the mothers in the Asian population were likely to adopt these feeding practices in response to their child’s BMI, rather than the converse.